Commercial and banking credit network in Uruguay - Andrea Barón; María Victoria Landaberry; Rodrigo Lluberas; Jorge Ponce (Latin American Journal of Central Banking (LAJCB), 2021)
We build a commercial credit network, identify the most central economic sectors in terms of commercial debt, and provide a more complete idea of total indebtedness and financial interlinks between firms and banks in Uruguay. "Commerce," "manufacturing," and "transportation, storage, and communication" are the most central sectors in the commercial credit network. In a stress testing exercise, "transportation, storage, and communication" and "hotels and restaurants" are deeply affected in all cases. These sectors are the most exposed in terms of contagion. "Commerce" and "manufacturing" are central and have the highest level of indebtedness, but they have a large amount of liquid assets, which allows them to overcome shocks from other sectors. The results highlight the importance of having a good estimation of commercial credit interlinks for financial stability analysis.
Keywords: G17; G32; G33; L14; 330; Commercial credit network; Financial interlinks; Financial contagion; Financial stability